INFLUENCE OF SMOKING ON THE METHYLIZING STATUS OF DESOXYRIBONUCLEIC ACID - A. V. Kiseleva; A. A. Zharikova; A. N. Meshkov (Кардиоваскулярная терапия и профилактика, 2015)
Smoking is one of the main factors of a wide range of diseases as ischemic heart disease, stroke, chronic obstructive pulmonary disease. To know mechanisms of smoking influence on the course of these diseases might lead to discovery of novel methods of diagnostics and prevention. Recent studies showed the impact of smoking on epigenetic mechanisms of heredity, particularly on the status of DNA methylizing. Current review focuses on the analysis of smoking influence of DNA methylizing. There are >60 genes described, methylizing of which is related to smoking. There is relation of methylizing level of genes AHRR, MMP25, PTGDS, WWC3, SASH1 not only with smoking but atherosclerosis.